1978
DOI: 10.3758/bf03329669
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in sucrose reward magnitude without generalization decrement

Abstract: Groups of albino rats were trained for 24 days in a straight runway with one of two different liquid sucrose concentrations, 30% or 3%, as reward. Training trials were administered 2/day with an intertrial interval (lTI) of 3·5 min. This preshift phase was followed by an additional 24 days in which both groups received the 3% solution. A significant main effect of reward magnitude developed early in the preshift phase and persisted throughout the postshift phase. Since the number of daily trials and the ITI em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The postshift conditions ended the preshift reward discrimination, unlike the earlier experiment, in which postshift trials were administered at 2 rather than 10 per day (Burns & Burns, 1978), but no clear SuNCE developed. The last tria1 of Day 1 in postshift could suggest contrast, but the lack of a Groups by Trials interaction coupled with (1) the results of a subsequent replication in which no crossover at all was observed (Burns, Note 1), and (2) the fact that the Trial 10 mean was unduly influenced by a single extreme score warrant the alternative interpretation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The postshift conditions ended the preshift reward discrimination, unlike the earlier experiment, in which postshift trials were administered at 2 rather than 10 per day (Burns & Burns, 1978), but no clear SuNCE developed. The last tria1 of Day 1 in postshift could suggest contrast, but the lack of a Groups by Trials interaction coupled with (1) the results of a subsequent replication in which no crossover at all was observed (Burns, Note 1), and (2) the fact that the Trial 10 mean was unduly influenced by a single extreme score warrant the alternative interpretation.…”
Section: Discussionmentioning
confidence: 91%
“…In a pair of experiments examining sequential learning in paradigms other than the contrast paradigm, Burns (1976) showed that sucrose traces are clearly differentiated under a restricted set of conditioning parameters, two trials per day with a 3-to 5-min intertrial interval (ITI), a result that implies that the SuNCE would occur with sucrose under the proper training conditions. Yet a shift from 30% sucrose to 3% sucrose failed to produce the SuNCE following training under these optimal aftereffect conditioning parameters (Burns & Burns, 1978). The postshift procedure of that sucrose-shift experiment did not, however, involve intentional confounding of the number of daily trials with changes in reward magnitude, but such a procedure is common in reward-sequence experiments involving shifts (e.g., Leonard, 1969).…”
Section: Methodsmentioning
confidence: 99%